Optimization and economic evaluation of ultrasound extraction of lutein from Chlorella vulgaris - Aree Deenu (2018)
The main carotenoid in Chlorella vulgaris is lutein. The ultrasound alone or together with enzymatic pretreatment for the extraction of lutein from C. vulgaris was optimized using response surface methodology (RSM) to improve the extraction process. The optimal ultrasound extraction condition was: ultrasound frequency, 35 kHz; ultrasound intensity, 56.58 W/cm 2 ; extraction temperature, 37.7 C; extraction time, 5 h; and ratio of solvent to solid, 31 mL/g, where the lutein recovery was 3.16 ± 0.03 mg/g wet C. vulgaris. The optimal enzymatic pretreatment was: reaction time, 2 h; enzyme concentration, 1.23% (v/w); pH, 4.5, and temperature 50 C. The optimal ultrasound extraction with enzymatic pretreatment was: ultrasound frequency, 35 kHz; ultrasound intensity, 56.58 W/cm 2 ; extraction temperature, 37.7 C; extraction time, 162 min; and ratio of solvent to solid, 35.6 mL/g wet C. vulgaris, where the extraction yield of lutein was 3.36 ± 0.10 mg/g wet C. vulgaris. This was much higher than for ultrasound treatment alone. The surface areas of microalga cells treated by ultrasound with/without enzymatic pretreatment increased significantly, which might contribute to the increase in lutein yield. There were no significant differences in structure, color, and antioxidant activity of lutein between the ultrasound and conventional methods. The highest cost of the crude and lutein was obtained by the ultrasound with enzymatic pretreatment due to the complex process and liquid waste in the enzymatic pretreatment process, but the ultrasound treatment alone was the lowest. Therefore, ultrasound extraction is the most economical method for the extraction of microalgal lutein. © 2013 The Korean Society for Biotechnology and Bioengineering and Springer-Verlag Berlin Heidelberg.